A buoyancy-based fiber Bragg grating tilt sensor - Maheshwari, Muneesh (2018)
In this paper, a novel design of fiber Bragg grating tilt sensor is proposed. This tilt sensor exhibits high angle sensitivity and resolution. The presented tilt sensor works on the principle of the force of buoyancy in a liquid. It has certain advantages over the other designs of tilt sensors. The temperature effect can be easily compensated by using an un-bonded or free FBG. An analytical model is established which correlates the Bragg wavelength (λB) with the angle of inclination. This model is then validated by the experiment, where the experimental and analytical results are found in good agreement with each other.